You need to evaluate the inverse function f^(-1)(x) such that:

y = (5x+6)/(5x+8) => y(5x + 8) = 5x + 6

5yx + 8y = 5x + 6

You need to isolate the terms that contain x to the left side, such that:

`5yx - 5x = 6 - 8y`

Factoring out 5x yields:

`5x(y - 1) = 6 - 8y => x = (6 - 8y)/(5y - 5)`

Hence, evaluating `f^(-1)(x)` yields:

`f^(-1)(x) = (6 - 8x)/(5x - 5)`

You may evaluate `f^(-1)(0)` such that:

`f^(-1)(0) = (6 - 8*0)/(5*0 - 5) => f^(-1)(0) = -6/5`

You may evaluate `f^(-1)(2)` such that:

`f^(-1)(2) = (6 - 8*2)/(5*2 - 5) => f^(-1)(0) = -10/5 = -2`

**Hence, evaluating `f^(-1)(0)` and `f^(-1)(2)` yields `f^(-1)(0) = -6/5` and **`f^(-1)(0) = -2.`